A comparison of fuzzy and non-fuzzy ordering heuristics for examination timetabling - Asmuni, Hishammuddin (2004)
The decision of `appropriately' choosing the order in which examinations are scheduled when constructing an examination timetable can be seen as a process of ordering alternatives from a set in order to find a good solution. In this paper, a comparison is made between fuzzy ordering with single and linear combinations of ordering heuristics. It is found that fuzzy ordering leads to better solutions.